illage Head Motivation in Improving Empowering Pottery Artisans in Sitiwinangun Village Jamblang District, Cirebon Regency - Anisah, Siti; Khumayah, Siti; Permana, Ipik (Jurnal Polisci, 2023)
Motivation is carried out by the head of the village for pottery artisans; in this case, the motivation is carried out to increase the empowerment of pottery crafts. The background of writing this thesis is to examine data and facts regarding the motivations of the village head for pottery artisans in increasing the empowerment of pottery handicraft products in Sitiwinangun Village, Jamblang District, Cirebon, West Java. The purpose of this research was to find out how the motivation and empowerment provided by the village head in improving community welfare, what kind of empowerment was carried out by the village head in improving community welfare, what obstacles were found by village officials in improving community welfare, what efforts were made by village officials in improving community welfare. The research method used by researchers in this study is descriptive qualitative. It is called a qualitative research method because this research uses qualitative data, namely data collected through library research and field studies, which include interviews, observation, and documentation. Based on the research results, the motivation of the village head in increasing the empowerment of pottery artisans as a whole has been carried out quite well.